The Challenges Confronting the Delivery of Training and Development Programs in Saudi Arabia: A Critical Review of Research - MAJED OTHAYMAN (American Journal of Industrial and Business Management, 2020)
This research aims to identify the challenges confronting the delivery of training and development in the context of Saudi Arabia. Saudi Arabia is a country which is currently in a transformational phase, triggered by domestic factors like Vision 2030 and global factors. Through a process known as Saudization, the government of Saudi Arabia seeks to improve the quality of human resource in the country and provide the maximum opportunities to its youth that constitutes a significant part of its population. To this end, the government is heavily investing in training and development programs and the education sector. This study collects secondary data from government documents, databases, articles, reports, books, and previous studies undertaken by the government to measure the effectiveness of its training and development programs. Various findings have been summarised from the perspective of challenges confronting the delivery of training and development programs in Saudi Arabia.